2019
DOI: 10.3389/fimmu.2019.01369
|View full text |Cite
|
Sign up to set email alerts
|

SPARC Is a New Myeloid-Derived Suppressor Cell Marker Licensing Suppressive Activities

Abstract: Myeloid-derived suppressor cells (MDSC) are well-known key negative regulators of the immune response during tumor growth, however scattered is the knowledge of their capacity to influence and adapt to the different tumor microenvironments and of the markers that identify those capacities. Here we show that the secreted protein acidic and rich in cysteine (SPARC) identifies in both human and mouse MDSC with immune suppressive capacity and pro-tumoral activities including the induction of epithelial-to-mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 42 publications
(60 reference statements)
3
35
0
Order By: Relevance
“…Recently, Sangaletti and collaborators demonstrated that impaired translocation of NF-κB p50 protein abolishes the secretion of protein acidic and rich in cysteine (SPARC) and alters MDSC-associated immunosuppression by limiting ROS production. Indeed, restricted p50 translocation into nucleus limits the formation of the immunosuppressive p50:p50 homodimers in favor of the p65:p50 inflammatory heterodimers that sustain an increased release of TNFα in the tumor microenvironment (47). According to this, we demonstrated that, the enhancement of nuclear p50 translocation by c-FLIP promotes acquisition of immunosuppressive function by monocytes (42).…”
Section: Mdsc: a Tumor-induced Myeloid Cell Subsetmentioning
confidence: 57%
See 2 more Smart Citations
“…Recently, Sangaletti and collaborators demonstrated that impaired translocation of NF-κB p50 protein abolishes the secretion of protein acidic and rich in cysteine (SPARC) and alters MDSC-associated immunosuppression by limiting ROS production. Indeed, restricted p50 translocation into nucleus limits the formation of the immunosuppressive p50:p50 homodimers in favor of the p65:p50 inflammatory heterodimers that sustain an increased release of TNFα in the tumor microenvironment (47). According to this, we demonstrated that, the enhancement of nuclear p50 translocation by c-FLIP promotes acquisition of immunosuppressive function by monocytes (42).…”
Section: Mdsc: a Tumor-induced Myeloid Cell Subsetmentioning
confidence: 57%
“…The MDSC plasticity and functions are strictly guided by the activation of precise signaling pathways [extensively reviewed in (8,45)] preferentially driven by c/EBPβ (CCAAT/enhancerbinding protein) (16), STAT3 (signal transducer and activator of transcription 3) (31,46) and NF-κB (42,47) transcriptional factors. c/EBPβ is the master regulator of "emergency" myelopoiesis and its critical role on MDSC biology was proved using myeloid-restricted c/EBPβ-deficient mice engrafted with different tumor models in which the ontogeny and MDSCassociated immunosuppression were completely abrogated (16).…”
Section: Mdsc: a Tumor-induced Myeloid Cell Subsetmentioning
confidence: 99%
See 1 more Smart Citation
“…SPARC and CXCR2 are two factors expressed in MDSCs and required for the acquisition of MDSC suppressive phenotype [62,64,65] . MDSC differentiation is facilitated by the tumor-derived cytokines, including G-CSF, GM-CSF, VEGF, and chemokines such as CCL2 and CXCL12 [62,[66][67][68][69] . Moreover, Thrombospondin 1 expression in the surface of MDSC-derived exosomes also causes MDSCs chemotaxis and migration [64] .…”
Section: Mdscsmentioning
confidence: 99%
“…Some divergent functions of SPARC reveal its complexity and underscore the context dependency of its activity, which strictly depends on tissue and cellular origin (Bradshaw, 2012). A under-investigated but interesting aspect of SPARC function, is the capacity of regulating the immune system in several aspects, such as dendritic cell migration and branching (Piconese et al, 2011), myeloidderived suppressor cell expansion and functional differentiation (Sangaletti et al, 2019) and B cell development (Luo et al, 2014;Sangaletti et al, 2014a). Studying mesenchymal cells functions in bone-marrow (BM) and secondary lymphoid organs we showed that the defective B cells development occurring in Sparc -/hosts under radiation-induced stress relies on SPARC limiting B cells precursors apoptosis (Sangaletti et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%